Manajemen Pengelolaan Dana ZIS pada LAZISMU Gresik: Analisis Efisiensi, Efektivitas, dan Kepercayaan Muzakki melalui SIMZISKA - Alfisyah, Ely Nur; Hasan, Dony Burhan Noor (Universitas Pamulang, 2025)
This study aims to analyze the management of Zakat, Infaq, Shodaqoh, and Religious Social Funds at LAZISMU Gresik Regency using the ZISKA Information System (SIMZISKA) and compare it with the Excel-based management system. The approach used is a descriptive method, with data collected through observation, interviews, and documentation. The results showed that implementing SIMZISKA significantly improved the efficiency and effectiveness of ZIS fund management. SIMZISKA enables better transparency and accountability in financial reports, minimizes errors through automation, and accelerates data processing that supports timely decision-making. Despite challenges related to system understanding and lack of training, the benefits gained, such as an increase in the amount of funds managed and muzakki trust, show that SIMZISKA is an effective solution for more efficient management of ZIS funds. Recommendations for system development include further training, developing SOPs, and adding features such as a data import-export menu and better internal controls